Effect Of Liquid Organic Fertilizer From Banana Waste On Growth And Years Criring Chili Plants (Capsicum Annum L) Trophy Hybrid Varieties - Budi Prastia; Pandu Tri Wardana; Setiono Setiono (Baselang, 2023)
Research on the Effect of Applying Liquid Organic Fertilizer from Plantain Waste on the Growth and Yield of Curly Chili (Capsicum annum L) Hybrid Trophy Varieties was carried out from January 1 2022 to May 1 2022. In the Community Agricultural Land in Sungai Keruh Village, Tebo Tengah District, it is located at an altitude of 121 m asl. With the aim to determine the effect of applying Liquid Organic Fertilizer (POC) from plantain waste and the best dose dosage on the growth and yield of curly chili (Capsicum annum L) trophy hybrid variety.              This experiment used a completely randomized design (CRD) which consisted of 5 treatments and 4 replications, with the following treatments: P0 (without applying liquid organic fertilizer), P1 (given POC (banana peel waste) at a dose of 400 ml/polybag), P2 (given POC (banana peel waste) at a dose of 500 ml/polybag), P3 (given POC (banana peel waste) at a dose of 600 ml/polybag) and P4 (given POC (banana peel waste) at a dose of 700 ml/polybag).  The above treatment was repeated 4 times (5 x 4 = 20 experimental units). Each experimental unit consisted of 3 plants so that 20 x 3 = 60 plants were obtained, all of the 3 plants per experimental unit were sampled.  The results and conclusions obtained are that the application of various doses of Liquid Organic Fertilizer (POC) from plantain waste has a significant effect on Plant Height (cm), Stem Circumference (cm), Total Leaf Area, Total number of fruits per plant (fruit), and Fruit weight per plant (gr) curly chili (Capsicum annum L). The best treatment for the growth of curly chili (Capsicum annum L) and the yield of curly chili (Capsicum annum L) of the trophy hybrid variety was P3 with a dose of 600 ml/polybag